Capital Structure, Profitability and Corporate Value: The Moderation Effect of Corporate Social Responsibility in Indonesian Sharia Companies - Riskin Hidayat; Khorunisa, Atikah Raid; Hermuningsih, Sri; Marhadi, Marhadi; Sarwar, Suleman (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2025)
This research explores the interactions among capital structure, profitability, and company value, with Corporate Social Responsibility (CSR) acting as a moderating factor. This investigation involves Sharia-compliant companies listed on the Jakarta Islamic Index (JII) of the Indonesia Stock Exchange (IDX) over the period from 2017 to 2022. Secondary data were collected from the annual reports of these companies. Employing a purposive sampling approach, the study analyzes a sample of 23 companies, yielding a total of 161 observations. To evaluate the data, moderated regression analysis was conducted using WarpPLS. The findings reveal that both capital structure and profitability exert a significant positive effect on company value, whereas CSR demonstrates an insignificant positive effect on company value. Moreover, CSR does not moderate the relationship between profitability and company value; however, CSR significantly moderates the relationship between capital structure and company value. These results highlight the critical role of capital structure and profitability in enhancing company value, particularly in the context of Sharia-compliant businesses, and contribute to both the growing body of literature and valuable insight for the supported stakeholders to optimize company performance.